Potwór jako zwierciadło herosa epickiego = Monster as the mirror of the epic hero - Zieliński, Karol (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In oral epic an image of the hero and his adversary is correlated. In the article there has been presented a model of the evolutionary transformation of the image of a monster in line with changes in the function and description of the hero. These changes correspond to the requirements of oral narrative structure, which is dynamic because singer?s main task is to build tension during performance of songs. The transition from the fairytale to historical epic marks the alignment of forces of the two warring parties, in which the adversary, losing monstrous scratches, takes over the individual elements of the hero (beginning from magical artifacts, which previously were to equal opportunities of the hero in the fight against the "dragon", and on the generosity of nature ending) becoming its mirror image.
Keywords: epika; tradycja oralna; heros; Achilles; Hektor; Memnon; artefakty magiczne; epic; oral tradition; hero; magical artifacts